SOME APPLICATIONS IN ECONOMICS (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Today for those who receive education in economic specialties (including second education), and meets the requirements of state educational standards for economic disciplines. The material is presented practically without proofs - the main emphasis is on acquiring skills in using the mathematical apparatus. Each issue is accompanied by numerous characteristic solutions to problems and relevant economic applications. Translated with DeepL.com (free version)